EFL student’s motivation in learning English in Langsa, Aceh - Maria Ulfa; Allif Syahputra Bania (Universitas Syiah Kuala, 2019)
The research deals with the intrinsic and extrinsic motivation of EFL learners in learning English. This research used the qualitative design to find out the EFL learners’ motivation in learning English, specifically to their intrinsic and extrinsic motivation. The participants consist of 40 senior high school students in Langsa. The questionnaire was the instrument used in collecting data. The questionnaire consists of 35 items, in which they are divided into two parts. The first part, numbers 1 until 20, is to collect the information about intrinsic motivation and inquires about interest, need, hobby and goal. Meanwhile, the second part, numbers 21 until 35, is to collect information about extrinsic motivation and inquires about teachers, parents, and the environment. The results showed that the component in the extrinsic motivation that gave the biggest impact to the students are the teachers; who are the student’s biggest influence in learning English. Meanwhile, the biggest component of intrinsic motivation is the students’ own learning goals. The paper further describes each of these factors in relation to their motivation. The implication of this study related to the teachers’ efforts and capability in motivating their students to learn English is also discussed.